2017
DOI: 10.1039/c7cc05495e
|View full text |Cite
|
Sign up to set email alerts
|

A novel metal–organic framework loaded with abundant N-(aminobutyl)-N-(ethylisoluminol) as a high-efficiency electrochemiluminescence indicator for sensitive detection of mucin1 on cancer cells

Abstract: Herein, a high-efficiency electrochemiluminescence (ECL) indicator of an abundant N-(aminobutyl)-N-(ethylisoluminol) functionalized metal-organic framework (ABEI@Fe-MIL-101) was synthesized to construct a biosensor for the ultrasensitive assay of mucin1 on MCF-7 cancer cells with a coreactant HO-free strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…[4] However, the low stability of H 2 O 2 at room temperature hampers the successful application of the luminol-H 2 O 2 ECL system. [5] Therefore, the search for durable co-reactants as alternatives to H 2 O 2 has been investigated.…”
mentioning
confidence: 99%
“…[4] However, the low stability of H 2 O 2 at room temperature hampers the successful application of the luminol-H 2 O 2 ECL system. [5] Therefore, the search for durable co-reactants as alternatives to H 2 O 2 has been investigated.…”
mentioning
confidence: 99%
“…It has been shown that ABEI can be easily incorporated in the skeleton of porous conducting polymer hydrogels, providing a short diffusion distance between the luminophore and the hydrogen peroxide coreactant, thereby realizing a sensitive in situ monitoring of the oxygen radicals released from cells [33]. It has also found application as a highly efficient ECL signal probe for cancer cell analysis [34].…”
Section: Luminol-based Systemsmentioning
confidence: 99%
“…However, the adopted synthesis involves multiple steps, desires tedious reactions without scalability. Moreover, the co-reactant like H 2 O 2 is also not quite stable at room temperature which also suppresses the efficiency of the ECL signal of luminol 16 . One can overcome this problem by generating the reactive oxygen species (ROS) by using co-reactant accelerators which can produce more ROS through the reduction of dissolved oxygen and enhances the stability of the ECL signal 17 .…”
Section: Introductionmentioning
confidence: 99%